Evaluasi Usability dan User Experience Pada E-Learning Universitas Sriwijaya Menggunakan Metode TUXEL 2.0 - A Salman Alfarizi; Dwi Rosa Indah; Mgs Afriyan Firdaus (STMIK Budi Darma, 2023)
The era of technology that continues to grow makes all work in life easier and more efficient. These developments have an impact on the world of education which innovates to create a learning style that can do learning whenever and wherever we want without the limitations of place and time with the help of technology called E-Learning. A website that functions as an E-Learning supporter is called a Learning Management System (LMS). Sriwijaya University already has an LMS called Sriwijaya University E-Learning. There are some problems and difficulties encountered in using E-Learning of Sriwijaya University. This is proven after the researcher conducted a pre-survey. The average answer stated strongly agree that Sriwijaya University E-Learning needs to be evaluated for usability and user experience. Furthermore, from the interview with the Coordinator of Learning Development Center (LP3MP UNSRI), the information was obtained that the need for input from users to make E-Learning better and to know the level of usability of E-Learning itself to continue to be used. The method used in this research is TUXEL 2.0 which consists of three stages namely Usability Inspection, General LMS/Pedagogical Usability Inspection, User Experience Evaluation. The sample used in this study was 150 students consisting of 15 people each per faculty. The result of usability inspection found 50 problems reported. while in General LMS/Pedagogical Usability Inspection there are total 33 problems found and in User Experience Evaluation stage, it is known that all aspect scales are > 0.8 means all aspects have positive level which indicates Sriwjaya University E-Learning is very good